Gender and water lifting technologies: water lifting irrigation and multiple purposes - Nigussie, Likimyelesh (International Water Management Institute, 2017)
Presented by Likimyelesh Nigussie (IWMI), as part of the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.